Effect of filament types and loops number on the force degradation of elastomeric chains used for orthodontic treatment: an in-vitro study - Bowen Zheng; Majedh Abdo Ali Al-Somairi; Zhiyuan Li; Yang Zhao; Yi Liu (BMC, 2023)
Abstract Background In orthodontic treatment, closing spaces, specifically the extraction and scattered spaces of the anterior teeth, requires some auxiliary bias, such as an elastomeric chain. Many factors affect the mechanical properties of elastic chains. In this study, we investigated the relationship of the filament type, the number of loops, and the force degradation of elastomeric chains under thermal cycling conditions. Methods The orthogonal design included three filament types (i.e., close, medium, and long). Four, five, and six loops of each elastomeric chain were stretched to have an initial force of 250 g in an artificial saliva environment at 37 °C and thermocycling between 5 and 55 °C three times a day. The remaining force of the elastomeric chains was recorded at different time points (4 h, 24 h, 7 days, 14 days, 21 days, and 28 days), and the percentage of the remaining force was calculated. Results The force decreased significantly in the initial 4 h and degraded mostly within the first 24 h. In addition, the percentage of force degradation increased slightly between 1 and 28 days. Conclusions Under the same initial force, the longer the connecting body is, the fewer the number of loops and the greater the force degradation of the elastomeric chain are.